Beyond Angels and Demons : The Truth Behind the Fiction - Chandelle, Rene (London Bounty Books, 2006)
A gripping tale of secret societies, from the time of Galileo Gallel to the present, the uneasy relationship between the Catholic Church and science, the mysteries and workings of the Vatican and plots for its destruction.
Include Glossary, Appendix and Colored Illustrations.
Keywords: Secret Societies -- Angels & Demons (Brown, Dan)